Multigenerational benign familial neonatal seizures with inadequate clinical response to levetiracetam - Aylward, Shawn C.; Gilbert, Donald L. (Journal of Pediatric Neurology, 2011)
Benign familial neonatal seizures is an autosomal dominant disorder characterized by generalized tonic-clonic or partial seizures beginning in the first three days of life. There have been two variants identified with defects in potassium channels, KCNQ2 and KCNQ3. We present a case of a 2-day-old male admitted with seizures. Upon obtaining a family medical history, it was discovered that there was a multigenerational history of neonatal seizures on the paternal side beginning at 3 days of life. The child underwent a full sepsis workup, magnetic resonance imaging, and interictal electroencephalography. He was discharged on levetiracetam at the parent’s request for a non-sedating medication, only to be re-admitted 36 hr later for continued seizures. He was eventually well controlled on phenobarbital, suggesting that levetiracetam may not be the optimal treatment for this condition.
Keywords: Benign neonatal epilepsy; benign familial neonatal seizures; KCNQ2; KCNQ3; levetiracetam; phenobarbital; fosphenytoin